MicroRNA-18a-5p Administration Suppresses Retinal Neovascularization by Targeting FGF1 and HIF1A - Guan, Ji-Tian; Li, Xin-Xin; Peng, De-Wei; Zhang, Wen-Meng; Qu, Jia; Lu, Fan; D’Amato, Robert J.; Chi, Zai-Long (Frontiers in Pharmacology, 2020)
Pathologic ocular neovascularization commonly results in visual impairment or even blindness in numerous fundus diseases, including proliferative diabetic retinopathy (PDR), retinopathy of prematurity (ROP), and age-related macular degeneration (AMD). MicroRNAs regulate angiogenesis through modulating target genes and disease progression, making them a new class of targets for drug discovery. In this study, we investigated the potential role of miR-18a-5p in retinal neovascularization using a mouse model of oxygen-induced proliferative retinopathy (OIR). We found that miR-18a-5p was highly expressed in the retina of pups as well as retinal endothelial cells, and was consistently down-regulated during retinal development. On the other hand, miR-18a-5p was increased significantly during pathologic neovascularization in the retinas of OIR mice. Moreover, intravitreal administration of miRNA mimic, agomiR-18a-5p, significantly suppressed retinal neovascularization in OIR models. Accordingly, agomir-18a-5p markedly suppressed human retinal microvascular endothelial cell (HRMEC) function including proliferation, migration, and tube formation ability. Additionally, we demonstrated that miR-18a-5p directly down-regulated known vascular growth factors, fibroblast growth factor 1 (FGF1) and hypoxia-inducible factor 1-alpha (HIF1A), as the target genes. In conclusion, miR-18a-5p may be a useful drug target for pathologic ocular neovascularization.